Art, creativity and resilience: resources in the face of the pandemic - Llanos Zuloaga, Martha (2020)
Art in its various forms, theater, narrative, music, circus, puppets, painting, ceramics, dance, movement and others, play a fundamental role in the processes of personal and social transformation. The Arts allows for expression, the power of humanization of the human beings has been proven since ancient time, giving emphasis within the area of human development. In this field, we see an evolution from the identification of art with an artistic product and with artists belonging to certain elites. Currently the concepts have evolved giving Art and Creativity a broader vision that generates educational, social and political processes. Art and Creativity play a crucial role in Resilience, concept currently widely spread because is a powerful valuable resource due to its impact on conflict resolution, in reinforcing internal strength and enhancing the necessary mechanisms to face crisis, uncertainty and trauma. The author has lived experiences with Theater of the Oppressed in India, Biodanza in Peru and Europe, Meditations in Movement, Narrative in Africa and Social Circus in Palestine. In 2019, she was invited by the World Alliance for Art Education to the world meeting held in Frankfurt, Germany to present her experiences in this field.